Dopamine D2-like receptors modulate unconditioned fear: role of the inferior colliculus. - Amanda Ribeiro de Oliveira; Ana Caroline Colombo; Sangu Muthuraju; Rafael Carvalho Almada; Marcus Lira Brandão (PLoS ONE, 2014)
BACKGROUND: A reduction of dopamine release or D2 receptor blockade in the terminal fields of the mesolimbic system clearly reduces conditioned fear. Injections of haloperidol, a preferential D2 receptor antagonist, into the inferior colliculus (IC) enhance the processing of unconditioned aversive information. However, a clear characterization of the interplay of D2 receptors in the mediation of unconditioned and conditioned fear is still lacking. METHODS: The present study investigated the effects of intra-IC injections of the D2 receptor-selective antagonist sulpiride on behavior in the elevated plus maze (EPM), auditory-evoked potentials (AEPs) to loud sounds recorded from the IC, fear-potentiated startle (FPS), and conditioned freezing. RESULTS: Intra-IC injections of sulpiride caused clear proaversive effects in the EPM and enhanced AEPs induced by loud auditory stimuli. Intra-IC sulpiride administration did not affect FPS or conditioned freezing. CONCLUSIONS: Dopamine D2-like receptors of the inferior colliculus play a role in the modulation of unconditioned aversive information but not in the fear-potentiated startle response.